2011
DOI: 10.2119/molmed.2011.00089
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Phase Protein α1-Antitrypsin Inhibits Neutrophil Calpain I and Induces Random Migration

Abstract: A rapid recruitment of neutrophils to sites of injury or infection is a hallmark of the inflammatory response and is required for effective host defense against pathogenic stimuli. However, neutrophil-mediated inflammation can also lead to chronic tissue destruction; therefore, a better understanding of the mechanisms underlying neutrophil influx and activation is of critical importance. We have previously shown that the acute phase protein α1-antitrypsin (AAT) inhibits neutrophil chemotaxis. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…More recent evidence has shown that M-AAT is a potent inactivator of fMLP induced neutrophil chemotaxis (Stockley et al 1990), in part thought to be due to its ability to inhibit protease involvement and thus effecting downstream events, such as cytoskeletal change and polarisation (Aoshiba et al 1991). This latter phenomenon is further supported by a recent study illustrating the ability of AAT to inactivate calpain-1 activity thereby inhibiting neutrophil directional migration (Al-Omari et al 2011). In addition, increased neutrophil numbers in the lungs of patients with AATD is thought in part due to a chemotactic process involving the alveolar macrophage.…”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Lung Dismentioning
confidence: 81%
See 1 more Smart Citation
“…More recent evidence has shown that M-AAT is a potent inactivator of fMLP induced neutrophil chemotaxis (Stockley et al 1990), in part thought to be due to its ability to inhibit protease involvement and thus effecting downstream events, such as cytoskeletal change and polarisation (Aoshiba et al 1991). This latter phenomenon is further supported by a recent study illustrating the ability of AAT to inactivate calpain-1 activity thereby inhibiting neutrophil directional migration (Al-Omari et al 2011). In addition, increased neutrophil numbers in the lungs of patients with AATD is thought in part due to a chemotactic process involving the alveolar macrophage.…”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Lung Dismentioning
confidence: 81%
“…Other serine proteases associated with coagulation (Gallimore 1975;Mast et al 1991), digestive enzymes (Beatty et al 1980), kalkriens derived from serum and tissue (Luo and Jiang 2006;Patston et al 1990) and urokinase (Clemmensen and Christensen 1976) are also inhibited by AAT. In addition, recent evidence has emerged on the ability of AAT to inhibit other classes of proteases including neutraland aspartic-cysteine proteases (Al-Omari et al 2011;Petrache et al 2006) and the matrix metalloprotease, ADAM-17 .…”
Section: Introductionmentioning
confidence: 99%
“…Serpin A1 has been shown to inhibit directional neutrophil migration towards the site of infection. 64 6. Serpin A1 inhibits the dissociation of NF-jb from Ijb, preventing migration of NF-jb to the nucleus and subsequent initiation of transcription of the HIV genes, thereby slowing the reproductive ability of HIV-1 as well as numerous other microbial species.…”
Section: Serpins Role In Hiv Infection and Inflammationmentioning
confidence: 99%
“…Serpins and cystatins are capable of limiting virus entry into target cells through either direct interference with binding of the virus to host cell receptors (AAT) 31 or prevention of target cell activation (AAT & serpin C1). 27 Serpin A3, AAT, cystatins A and B are all responsible for reducing the level of efficient chemotactic ability of various target cells through control of pro-inflammatory proteases at the site of infection, 27,64 which in turn reduces the amount of available HIV target cells. For those cells that do become infected by HIV, they are offered increased protection from apoptosis by cystatin A 65 and reduction in viral replication via interference of AAT C-terminal fragment with the NF-kb pathway.…”
Section: Predictive Model For the Role Of Antiproteases At Mucosal Sumentioning
confidence: 99%
“…[9][10][11] Over the past 15 years it has been shown that, besides inhibiting proteases, AAT has relevant anti-inflammatory and immunomodulatory properties, modulating the activity of various key cells of the immune system such as neutrophils, lymphocytes, monocytes, macrophages and mast cells, as well as fibroblasts and epithelial cells. [12][13][14][15][16][17][18][19][20][21][22] AAT therapy was found to be beneficial in a wide range of experimental models, where it protected islet cell allografts from rejection, [23][24][25][26] prevented graft-versus-host-disease, 27,28 delayed rheumatoid arthritis development, 29 protected from acute myocardial and renal ischaemia reperfusion injury, 30 inhibited acute liver failure 31 and protected against tumour necrosis factor (TNF)-a/ endotoxin-induced lethality. [32][33][34] In addition to its use in emphysema, intravenous augmentation of AAT has been found to be effective in single cases and small cohorts with panniculitis, vasculitis, fibromyalgia and cystic fibrosis.…”
Section: Xy Haplotype (Male)mentioning
confidence: 99%